2021
DOI: 10.3390/geosciences11020089
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Degree of Saturation (DOS) on Dynamic Behavior of Unbound Granular Materials

Abstract: The extensive application of natural unbound granular materials (UGMs) motivates studies into the mechanical properties of alternatives such as processed crushed rocks employed commonly as base or subbase layers. The rutting and settlement generated in base and subbase layers is widely restricted in many specifications and standards. In this research, the dynamic behavior including the resilient modulus () and the plastic strain () of the crushed rocks collected from Queensland in Australia will be tested by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Another study indicated that changes in fine and moisture content have a major influence on the permanent and resilient deformation of granular material [6]. Other researchers have observed that unbound granular material specimens samples soaked at a higher degree of saturation caused lower resilient modulus and had little resistance to heavy traffic [7]. Another study revealed that an increase in moisture content significantly decreases the resiliency of material [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that changes in fine and moisture content have a major influence on the permanent and resilient deformation of granular material [6]. Other researchers have observed that unbound granular material specimens samples soaked at a higher degree of saturation caused lower resilient modulus and had little resistance to heavy traffic [7]. Another study revealed that an increase in moisture content significantly decreases the resiliency of material [8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, advancements in technology have influenced how designs are conceptualized, considering sustainability aspects [1][2][3][4], challenges faced in laboratory soil tests [5,6], soil-structure simulations [7,8], and inferior in situ geomaterial conditions requiring biological [9][10][11][12][13][14] or chemical stabilization [15][16][17]. For instance, the study of the effects of the interface on soil-structure interactions have benefitted from this technological advancement to include the design of deep foundations [18][19][20][21][22][23], pavement-subgrade behavior [24,25], tunneling [26][27][28][29][30][31][32][33], mechanically stabilized geogrid retaining walls, and ground improvement in soft soils [34][35][36]. For example, in the design of deep foundations, static and dynamic pile load tests provide the necessary evidence-based field observational results to verify the accuracy and reliability of the initially adopted pile design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of soils and rocks forms the basis in any infrastructure and underground space construction works (Ong et al, 2003b, Ong and Choo, 2011Sun et al 2021) including pipe-jacking or shaft construction works but not without challenges faced in interpreting laboratory tests (Mehdizadeh et al, 2016(Mehdizadeh et al, , 2017Peerun et al 2019, Wong et al, 2017 and inferior structure / soil conditions requiring conditioning and improvement (Leong et al, 2015(Leong et al, , 2016a(Leong et al, , 2016b(Leong et al, , 2018a(Leong et al, , 2018bOmoregie et al, 2020Omoregie et al, , 2019aOmoregie et al, , 2019bOmoregie et al, , 2019cOmoregie et al, , 2017Omoregie et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%